Research on accessibility of port collection and distribution system from the perspective of carbon emissions - Wang, Guangsheng; Song, Yuheng; Yu, Tong; Lei, Zhiyi; Yang, Yanhao; Huang, Guangyu (Frontiers in Marine Science, 2023)
Port accessibility is an important factor in the efficiency of a port collection and distribution systems. And the carbon emission of the collection and transportation system is large, which is an important factor that cannot be ignored when constructing the collection and transportation system. In order to analyze the carbon emission characteristics of the port collection and distribution system, the paper incorporates the carbon emission factor into the accessibility measurement of the port collection and distribution system. To solve the problem of unbalanced demand of each logistics node, the distribution of logistics demand in the system is realized by the method based on the appropriate freight volume. The carbon emission cost factor is introduced, and the accessibility measurement model based on the generalized cost impedance function is constructed. Taking the collection and distribution system of Douala Port in West Africa as an example to verify, the results show that, after adding the carbon emission factor, the accessibility of each logistics node shows different degrees of decline which shows that the addition of the carbon emission factor can be more comprehensive and can reflect the accessibility of the system.